Hydrothermal carbonization synthesis and KOH activation of porous carbons from waste marigold flowers - N Chaiammart; A Eiad-ua; G Panomsuwan (My University, 2020)
Abstract Marigold flower-derived porous carbons were synthesized via hydrothermal carbonization (HTC) and KOH activation. The effect of HTC and KOH activation on the change in morphology, chemical functional group, and surface area were studied and discussed based on the results of scanning electron microscopy, Fourier transform infrared spectroscopy, and N 2 sorption analysis, respectively. Both HTC and KOH activation were found to play critical roles in changing morphology and enhancing surface area. Without HTC and KOH activation, carbons had low surface area and lacked porosity. In contrast, with both HTC and KOH activation, a sponge-like morphology with a large specific surface area of 1825 m 2 /g was obtained. The results serve as a useful guideline for further development and synthesis of porous carbons in certain specific applications.
Keywords: Hydrothermal Carbonization; Morphology; Specific surface area; Supercapacitor Materials and Fabrication